2022
DOI: 10.1097/rct.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Diagnostic Radiology: Where Do We Stand, Challenges, and Opportunities

Abstract: Artificial intelligence (AI) is the most revolutionizing development in the health care industry in the current decade, with diagnostic imaging having the greatest share in such development. Machine learning and deep learning (DL) are subclasses of AI that show breakthrough performance in image analysis. They have become the state of the art in the field of image classification and recognition. Machine learning deals with the extraction of the important characteristic features from images, whereas DL uses neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…In line with the first objective of the study, we analysed the main challenges in the design and integration of Artificial Intelligence in digital radiology. The eligibility process led to the choice of 20 papers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], among which there are mainly reviews (15 in number) (as it could be expected considering the broad topics covered) but also 5 recent scientific articles/focus articles on very specific aspects [ 15 , 26 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the first objective of the study, we analysed the main challenges in the design and integration of Artificial Intelligence in digital radiology. The eligibility process led to the choice of 20 papers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], among which there are mainly reviews (15 in number) (as it could be expected considering the broad topics covered) but also 5 recent scientific articles/focus articles on very specific aspects [ 15 , 26 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Maowad et al [ 12 ] specifically focused on the challenges of machine learning and deep learning, subclasses of Artificial Intelligence that showed breakthrough performance in image analysis. The authors discussed the current applications of machine learning and deep learning in the field of diagnostic radiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, work can be found that uses the concept of artificially generated negative data to form decision using a multilayer perceptron [ 35 ]. A few models of neural networks are known, e.g., Convolutional Neural Networks (CNNs) [ 36 , 37 ], Recurrent Neural Networks (RNNs) [ 38 ], Generative Adversarial Networks (GANs) [ 39 ], and Quantitative Susceptibility Mapping (QSM) [ 40 , 41 ]. Particularly, CNNs were most widely used for MRI and other image processing applications.…”
Section: Discussionmentioning
confidence: 99%
“…The recording of the surgical field and the operative environment is increasingly common, with the increase in minimally invasive and robotic surgery necessitating an endoscope. AI through data science has shown to be able to develop the ability to distinguish and diagnose pathology from medical imaging [ 78 ], to recognise anatomical structures from operative footage [ 79 ] and to replicate and automate the performance of surgical tasks [ 80 ]. Regarding the surgical workflow, benefits would be seen with hospital schedules with the ability to predict surgical phases in real time, giving surgical staff a greater awareness of remaining procedural time [ 81 ].…”
Section: Methodsmentioning
confidence: 99%